The role of production technology for productivity spillovers from multinationals: firm-level evidence for Hungary - Holger Görg; Alexander Hijzen; Balázs Muraközy (Kiel Institute for the World Economy (IfW), 2009)
This paper analyses the potential for productivity spillovers from inward foreign direct investment using administrative panel data on firms for Hungary. We hypothesise that the potential for spillovers is related to observable characteristics of the production process of foreign affiliates, and evaluate this empirically. We further explore the role of competition in explaining productivity spillovers within industries. Our empirical analysis yields a number of important findings. First, we show that the potential for spillovers is importantly related to the production technology of the sectors and foreign affiliates. Firms that relocate labour-intensive activities to Hungary to exploit differences in labour costs are unlikely to generate productivity spillovers, while spillovers increase in the capital intensity of foreign affiliates. Second, we find that spillovers differ markedly in the early and later stages of transition, and that there are differences between small and large firms. Furthermore, foreign presence tends to affect the productivity of domestic firms negatively whenever MNEs produce for the domestic market.
Keywords: F23; 330; Foreign direct investment; productivity spillovers; exporting; competition; Direktinvestition; Produktivität; Spillover-Effekt; Multinationales Unternehmen; Fertigungstechnik; Export; Internationaler Wettbewerb; Ungarn